Two 3D Rubidium Halide Organic–Inorganic Hybrid Perovskite Ferroelectrics Templated by Quasi‐Spherical Organic Amine 1, 4‐Diazabicyclo[3.2.2]nonane. Issue 71 (27th October 2022) - Wei, Jing; Han, Keke; You, Xiuli; Zhang, Mengxia; Wei, Zhenhong; Zhang, Haina; Cai, Hu
Abstract: The emergence of (CH3 NH3 )PbI3 has brought the development of three‐dimensional (3D) organic‐inorganic hybrid perovskite (OIHP) structures with ABX3 type to a higher level; however, most 3D frameworks are constructed by corner‐sharing of BX6 octahedra. Herein, we substituted the spherical molecule 1, 4‐diazabicyclo[2.2.2]octane (2.2.2‐dabco) with 1, 4‐diazabicyclo[3.2.2]nonane (1, 4‐3.2.2‐dabcn) as a template to react with RbX (X=Br, I) in the corresponding HX acids under the consideration of reducing the molecular symmetry. Two 3D OIHP compounds [1, 4‐3.2.2‐H2 dabcn]RbI3 ⋅H2 O (1 ) and [1, 4‐3.2.2‐H2 dabcn]RbBr3 (2 ) crystallized in non‐centrosymmetric point group mm 2 before the phase transition point were isolated. Among them, the 3D inorganic framework of 1 is constructed by sharing the corner of [RbI6 ] octahedra, while that of 2 is constructed by sharing the corner and face of [RbBr6 ] octahedra to acquire large cavities to accommodate the organic amine cation [1, 4‐3.2.2‐H2 dabcn] 2+ ; this 3D framework type is unprecedented in the OIHPs. As expected, compounds 1 and 2 exhibit reversible phase transition, dielectric and second harmonic generation (SHG) and ferroelectric properties, in which the phase transition temperature of 2 at 374 K is much higher than compound 1 at 280 K. Abstract : Two 3D organic–inorganic hybrid ABX3 perovskite structures constructed with [RbX6 ] (X=Br, I) octahedra by sharing corner or face can accommodate the large spherical organic molecule 1, 4‐diazabicyclo[3.2.2]nonane using the different cavities in their inorganic frameworks.